Classification of Inheritance Shop Houses in George Town, Penang - UNESCO World Heritage Site - Mansor, Rozliani; Othuman Mydin, Md Azree; Md. Sani @ Abd. Rahim, Norazmawati; Roosli, Ruhizal; Hassan, Hasnanywati (Eftimie Murgu University of Resita, 2012)
Shop house is an urban terrace house attribute of Asian towns from the 18th century which usually integrates a shop or business premise on the ground floor whilst the family dwells on the upper level, providing both ease and safety. The shop house might also be used entirely as dwelling quarters. Shop houses are constructed in rows and each row is arranged in blocks enclosed within a grid of main roads, back lanes and side roads. A shop house is usually two or three storeys high and is long and narrow, sharing a party wall with neighbours on either side. The Penang shop house is a ideal paradigm of a green building, using materials that are locally obtainable such as lime, clay stone and timber and suited to local geology and weather conditions. Shop houses also possessing architectural characteristics such as air vents and air-well that assist with natural ventilation and cooling. This paper will discuss categories and styles of the shop houses in historic city of George Town which can be divided into nine major groups.